Introductory fluid mechanics for physicists and mathematecians - Pert, Geoffrey J. (New York : Wiley, 2013)
This textbook presents essential methodology for physicists of the theory and applications of fluid mechanics within a single volume. Building steadily through a syllabus, it will be relevant to almost all undergraduate physics degrees which include an option on hydrodynamics, or a course in which hydrodynamics figures prominently.
Cover; Title Page; Copyright; Contents; Preface; Chapter 1 Introduction; 1.1 Fluids as a State of Matter; 1.2 The Fundamental Equations for Flow of a Dissipationless Fluid; 1.3 Lagrangian Frame; 1.3.1 Conservation of Mass; 1.3.2 Conservation of Momentum-Euler's Equation; 1.3.3 Conservation of Angular Momentum; 1.3.4 Conservation of Energy; 1.3.5 Conservation of Entropy; 1.4 Eulerian Frame; 1.4.1 Conservation of Mass-Equation of Continuity; 1.4.2 Conservation of Momentum; 1.4.3 Conservation of Angular Momentum; 1.4.4 Conservation of Energy; 1.4.5 Conservation of Entropy; 1.5 Hydrostatics. 1.5.1 Isothermal Fluid-Thermal and Mechanical Equilibrium1.5.2 Adiabatic Fluid-Lapse Rate; 1.5.3 Stability of an Equilibrium Configuration; 1.6 Streamlines; 1.7 Bernoulli's Equation: Weak Form; 1.8 Polytropic Gases; 1.8.1 Applications of Bernoulli's Theorem; 1.8.1.1 Vena Contracta; 1.8.1.2 Flow of gas along a pipe of varying cross-section; Case study 1.I Munroe Effect-Shaped Charge Explosive; Chapter 2 Flow of Ideal Fluids; 2.1 Introduction; 2.2 Kelvin's Theorem; 2.2.1 Vorticity and Helmholtz's Theorems; 2.2.1.1 Simple or rectilinear vortex; 2.2.1.2 Vortex sheet; 2.3 Irrotational Flow. 2.3.1 Crocco's Equation2.4 Irrotational Flow-Velocity Potential and the Strong Form of Bernoulli's Equation; 2.5 Incompressible Flow-Streamfunction; 2.5.1 Planar Systems; 2.5.2 Axisymmetric Flow-Stokes Streamfunction; 2.6 Irrotational Incompressible Flow; 2.6.1 Simply and Multiply Connected Spaces; 2.7 Induced Velocity; 2.7.1 Streamlined Flow around a Body Treated as a Vortex Sheet; 2.8 Sources and Sinks; 2.8.1 Doublet Sources; 2.8.1.1 Doublet sheets; 2.8.2 Flow Around a Body Treated as a Source Sheet; 2.8.3 Irrotational Incompressible Flow Around a Sphere; Case study 2.I Rankine Ovals. 2.9 Two-Dimensional Flow2.9.1 Irrotational Incompressible Flow; 2.10 Applications of Analytic Functions in Fluid Mechanics; 2.10.1 Flow from a Simple Source and a Simple Vortex; 2.10.1.1 Free vortex; 2.10.1.2 Two-dimensional doublets and vortex loops; 2.10.2 Flow Around a Body Treated as a Sheet of Complex Sources and Doublets; Case study 2. II Application of Complex Function Analysis to the Flow around a Thin Wing; 2.10.3 Flow Around a Cylinder with Zero Circulation; 2.10.4 Flow Around a Cylinder with Circulation; 2.10.5 The Flow Around a Corner. 2.11 Force on a Body in Steady Two-Dimensional Incompressible Ideal Flow2.12 Conformal Transforms; Appendix 2.A Drag in Ideal Flow; 2.A.1 Helmholtz's Flow and Separation; 2.A.2 Lines of Vortices; 2.A.2.1 Single infinite row of vortices; 2.A.2.2 Two parallel symmetric rows of vortices; 2.A.2.3 Two parallel alternating rows of vortices; Chapter 3 Viscous Fluids; 3.1 Basic Concept of Viscosity; 3.2 Differential Motion of a Fluid Element; 3.3 Strain Rate; 3.4 Stress; 3.5 Viscous Stress; 3.5.1 Momentum Equation; 3.5.2 Energy Equation; 3.5.3 Entropy Creation Rate.
3.6 Incompressible Flow-Navier-Stokes Equation.
Includes index.
Keywords: FLUID MECHANICS